INVESTIGATION OF CHANGES IN POLYMER-PROBE INTERACTIONS WITH STABILIZATION TEMPERATURE OF A COLUMN CONTAINED ACRYLONITRILE-METHYLACRYLATE-SODIUM-2-ACRYLAMIDO-2-METHYL PROPANE-1-SULFONATE COPOLYMER BY INVERSE GAS-CHROMATOGRAPHY - COSKUN, M; KAYA, I; OZDEMIR, E (Marcel Dekker Inc, 1993)
A column filled with Chromosorb W coated with the copolymer acrylonitrile(AN), methylacrylate(MA) and sodium-2-acrylamido-2-methyl propan-1-sulfonate(SAMPS) with a mole ratio of 90.3%, 9.1% and 0,6%, respectively, was conditioned at 150-degrees-C, 175-degrees-C, 200-degrees-C and 260-degrees-C under nitrogen current. After each stabilization, the retention diagrams as plots of in V(g) against 1/T were determined by using inverse gas chromatography(I.G.C.) technique and N,N-dimethylformamide(N,N-DMF), pyridine, 1-propanol and p-xylene as probes in the temperature range 50-150-degrees-C. A film of AN-MA-SAMPS copolymer was heated in an oven at 150-degrees-C, 175-degrees-C, 200-degrees-C and 260-degrees-C under nitrogen current which these conditions are the same those of coated copolymer in the column. After each heating, the IR spectrum, the TG and the DTA curves of the film copolymer were recorded.The changes in structure of the copolymer and solid phase transations suggested by the retention diagrams and the DTA curves were discussed.
Keywords: Thermal-Degradation; Polyacrylonitrile; Pyrolysis; State